2019
DOI: 10.1002/mmce.21830
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarized stacked patch antenna array with enhanced bandwidth for S‐band applications

Abstract: This paper demonstrates the design procedure of a 4 × 8 phased array antenna. Initially, a unit element in multilayer topology with orthogonal slots in the ground plane to couple electromagnetic energy is designed. Then, a stacked patch with truncated edges is placed on the top thick substrate layer to enhance the bandwidth to 600 MHz. This multilayered stacked patch unit element is then used to design a 1 × 4 and 4 × 8 slot coupled stacked patch array. On the bottom side, a novel feedline structure is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this, some recent studies have been reported on the slot loading effect on the antenna current polarization in [23], [26]- [29]. In general, dual band circularly polarised antennas are found to be a popular choice for WLAN, Wi-Fi, and global positioning satellite applications [30]. In the earlier stage, aperture coupled stacked microstrip patches were used to achieve the dual band CP operation in [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…In this, some recent studies have been reported on the slot loading effect on the antenna current polarization in [23], [26]- [29]. In general, dual band circularly polarised antennas are found to be a popular choice for WLAN, Wi-Fi, and global positioning satellite applications [30]. In the earlier stage, aperture coupled stacked microstrip patches were used to achieve the dual band CP operation in [31], [32].…”
Section: Introductionmentioning
confidence: 99%